Antiseptic activity evaluation of piper leave from Piper betle Linn extract in hand gel antiseptic preparation - Sari, Retno; Isadiartuti, Dewi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
It is known that piper leaves (sirih) from Piper betle Linn has been used traditionally as medicine, for example for mouthwash and wound curing. The usage of hand gels antiseptic preparation was getting increased in the current time as the incidence of desease caused by virus and bacteria like SARS appears.This research was aimed to develop preparation of hand gels from piper leaves extract obtained from extraction with hot water. The formulation of gels were made using 5%, 10%, 15%, 20% and 25% of piper leaves extract in Carbopol gel base. The evaluation of antiseptics activity was carried out using the Replica method. A series of test was done by pouring the gels at hand palm and slightly tap the thumb fingerprint to nutrient agar media. The media was incubated at 37°C for 24 hours,and the number of colonies of microorganism was counted. The antiseptic activity of the gels also compared with two hand gels antiseptic preparation containing ethanol and triclosan as antiseptic agentThe result showed that the piper leaves extract gels had a transparent pale yellow performance. The gel preparation with concentration of 15% extract had activity to reduce the microorganism of skin normal flora up to 50%. Yet the 25% concentration of piper leave extract could eliminate all the microorganism. It was also known that the 15% piper leaves extract gel had no significance different with the ethanol preparation, since the 20% and 25% piper leaves extract gels had similar antiseptic activity to the triclosan preparation.Key words: piper leaves extract, gel, antiseptic activity, replica methods